Fiziceskaja podgotovka vysokokvalificirovannych tjaželoatletov s primeneniem trenažera «Pravilo» - Belyaev, V. S.; Bogutskiy, S. V.; Tusher, Yu. L.; Chernogorov, D. N. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2017)
In the article the authors present the modern approach to the organization of the general physical training of weightlifters of high qualification with the use of a complex of general physical training of weightlifters of high qualification using the complex of exercises on the simulator "Rule" and the influence of these complexes on the growth of the level of special physical fitness and the psychophysical state of the athletes.